2012
DOI: 10.2527/jas.2011-4511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of castration technique on beef calf performance, feed efficiency, and inflammatory response1

Abstract: The objective of this experiment was to examine the effect of castration technique on daily feed intake (DFI), daily water intake (DWI), growth performance, residual feed intake (RFI), and inflammatory response in weaned beef calves. Seventy-five beef calves (214 ± 3.2 kg; 200 ± 26 d of age) were housed in a GrowSafe 4000 feed intake facility 7 d post weaning (15 calves/pen). Calves were offered a total mixed ration (TDN = 67.3% and CP = 12.2%, DM = 89%) for ad libitum consumption. On d 0, calves were assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 23 publications
4
14
0
2
Order By: Relevance
“…This is in agreement with studies previously reviewed (Bretschneider, 2005) and others not included in that review (Fenton et al, 1958;Fell et al, 1986;Warnock et al, 2012). Another study not included in that review reported significantly superior ADG (by about 0.3 kg/day) to weaning (timing not reported) in calves ring castrated at 2-3 months of age compared with calves surgically castrated or left intact (Lents et al, 2001).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is in agreement with studies previously reviewed (Bretschneider, 2005) and others not included in that review (Fenton et al, 1958;Fell et al, 1986;Warnock et al, 2012). Another study not included in that review reported significantly superior ADG (by about 0.3 kg/day) to weaning (timing not reported) in calves ring castrated at 2-3 months of age compared with calves surgically castrated or left intact (Lents et al, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…In the longer-term, whilst haptoglobin concentrations steadily declined in the surgical castrates, they were significantly elevated at 14 days post-castration in the Ring calves of both age groups. This difference between methods in the pattern of the inflammatory response is supported by the findings of others (Fenton et al, 1958;Molony et al, 1995;Carragher et al, 1997;Warnock et al, 2012). The inflammatory response appeared related to the rate of wound healing as, at days 14 and 21, there were indications of infection and poor healing in the Ring calves and particularly in the 6-month-old calves.…”
Section: Discussionsupporting
confidence: 60%
“…5 Escala de 1 a 9 pontos, na qual maior valor representa carne com maior maciez. 6 Escala de 1 a 9 pontos, na qual maior valor representa carne com melhor palatabilidade. 7 Escala de 1 a 9 pontos, na qual maior valor representa carne com maior suculência.…”
Section: Resultsunclassified
“…Hill 23 também cita que a gordura intramuscular é a primeira a ser mobilizada em condições de deficiência nutricional 28 , o que poderia ter ocorrido nos animais deste trabalho, principalmente nos castrados.…”
Section: Resultsunclassified
“…In steer production systems, castration is, apart from weaning, the major management procedure causing distress in calves, which can lead to reduced feed intake, growth rates and even weight loss during the first weeks after the procedures are conducted (Arthington et al, 2003;Ting et al, 2005;Warnock et al, 2012).…”
Section: Introductionmentioning
confidence: 99%